(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Oral route delivery of many non-steroidal anti-inflammatory drugs possessing poor gastrointestinal fluid solubility is associated with low gastrointestinal absorption and poor bioavailability. Nanoparticle technologies are being employed as effective techniques to overcome the challenge of poor aqueous solubility of many drugs. The study aimed at utilizing cow fat as solid-lipid nanocarrier system to enhance the aqueous solubility of diclofenac. Preformulation studies including melting points, gas chromatography-mass spectrophotometery, dynamic scanning calorimetry and Fourier transform infrared spectroscopy were carried out on the cow fat prior to product preparations Six (6) diclofenac-loaded solid lipid nanoparticle formulations containing varied proportions of stearic acid, cow fat and selected surfactants were prepared by the hot homogenization and ultra-sonication processes. The resulting preparations were characterized for surface morphology, particle size distribution, drug loading efficiency and drug release profiles. Thereafter, the SLNs were lyophilized and filled into number 4 empty gelatin capsule shells for further studies. The melting point of the fat was 43.13 ± 0.64 oC. Spectral analyses of the optimized SLN formulation revealed the existence of smooth surface with amorphous texture. The mean particle size of the SLNs formulated with stearic acid as solid lipid was in the range of 56.28 ± 0.56 - 100.23 ± 0.37 nm while formulations prepared with cow fat had their mean particles sizes ranging from 97.24 ± 04 to 171.29 ± 0.08 nm. The drug loading efficiencies of various formulations ranged from 72.32 ± 0.97 – 94.43 ± 0.11 % with the rate of releases being formulation component dependent...